Carnidae (Diptera) in the Canadian National Collection of Insects (Ottawa), with the description of five new species - Stuke, Jens-Hermann (Zootaxa, 2016)
The previously unidentified Carnidae in the Canadian National Collection of Insects (Ottawa) have been investigated. All faunistic records of 26 species are presented in this paper. Hemeromyia alberichae spec. nov. (USA), Meoneura hobbitoides spec. nov. (USA), Meoneura swifti spec. nov. (USA), Meoneura tinkerbellae spec. nov. (Canada), and Meoneura yodai spec. nov. (Canada) are described. First records are reported for Argentina, Canada, and Lebanon.